Asuhan Kebidanan Berkelanjutan Ny. "A" di Puskesmas Antang Perumnas Tahun 2025 - Nirwana; Endang Sulistyowati; Jumriana Ibriani; Srimarda J. Rahim (BIDANA: Jurnal Ilmu dan Praktik Kebidanan, 2026)
Continuity of Midwifery Care (CMC) is continuous midwifery care from pregnancy through family planning that aims to detect problems early and reduce maternal and infant mortality. This case study aimed to provide continuous midwifery care for Mrs. "A" G1P0A0 from pregnancy to family planning at Antang Perumnas Primary Health Center, using the Varney midwifery management approach and SOAP documentation accompanied by home visits, conducted from March to June 2025. Mrs. "A", aged 24, attended six antenatal visits with a fundal height of 32 cm, an estimated fetal weight of 3,100 grams, and normal laboratory findings. Labour was normal: first stage 8 hours, second stage 45 minutes, third stage 10 minutes, and fourth stage 2 hours. A male infant was born spontaneously on 9 May 2025 with an APGAR score of 8/10, weighing 3,200 grams and measuring 48 cm, without congenital abnormalities. The postpartum and neonatal periods were normal, and the mother chose a three-month injectable contraceptive. Continuity of Midwifery Care for Mrs. "A" was comprehensively implemented from pregnancy, childbirth, and the postpartum period through the newborn stage without complications. The CMC approach proved effective in monitoring and improving maternal and infant health while supporting the government programme to reduce maternal and infant mortality in Indonesia. Keywords: Continuity of Midwifery Care; family planning; newborn; normal childbirth; postpartum period; pregnancy